Semi-Image Neighborhood Block Graphs with Crossing Numbers - Niranjan, K. M.; Nagaraja, P.; V, Lokesh (Journal of Scientific Research, 2013)
The advent of graph theory has played a prominent role in wide variety of engineering applications. Minimization of crossing numbers in graphs optimizes its use in many applications. In this paper, we establish the necessary and sufficient condition for Semi-Image neighborhood block graph to have crossing number 3. We also prove that the Semi-Image neighborhood block graph NBI(G) of a graph never has crossing numbers k, where 1 ? k ? 6. Keywords: Semi-Image; Neighborhood block; Crossing numbers. © 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v5i2.11019 J. Sci. Res. 5 (2), 295-299 (2013)